Pendampingan Remaja di Kabupaten Kuningan Jawa Barat dalam Penggunaan Media Sosial Instagram sebagai Pelestarian Budaya - Murtanti Putri, Dianingtyas; Jamilah Mihardja, Eli; Mulyasari Agustini, Prima (LPkM Universitas Bakrie, 2019)
The entry of the current 4.0 era known as the era of disruption that requires various aspects to go forward and be able to follow the development of technological progress. It takes innovation, problem-solving, and creativity to face this era of disruption. One aspect is the promotion of Indonesia culture as a national identity which is still limited using a variety of conventional media, which must be changed immediately. Social networking media is an effective means to promote diverse cultures of the archipelago, young users dominate internet users in Indonesia, especially social networking media. In this community service program, giving an understanding in the form of in-depth counseling about the identity and preservation of local cultural values, followed by training in the use of social media, especially Instagram to increase awareness of millennial and Gen Z teenagers about the preservation of the local culture they have. The existence of training and counseling on the use of social media as preservation of local culture namely Kuningan, West Java through the promotion of local culture with Instagram as the medium, it is hoped that after attending the training they will be able to implement Instagram as a means of promoting Kuningan’s local culture.